The ecology and dynamics of ice wedge degradation in high-centre polygonal terrain in the uplands of the Mackenzie Delta region, Northwest Territories - Steedman, Audrey Elizabeth (2014)
Climate warming has the potential to alter the structure and function of Arctic ecosystems in ways that are not fully understood. Polygonal terrain is a widespread permafrost feature of Arctic landscapes that is likely to be impacted by warming ground temperatures. This is of particular relevance in the uplands in the Mackenzie Delta region, where high-centre ice wedge polygon fields comprise 10% of the terrestrial landscape, and mean annual ground temperatures have increased between 1 and 2°C over the last 40 years (Burn and Kokelj 2009). I used broad-scale airphoto analysis and fine-scale field studies to investigate the impacts and possible trajectories of ice wedge degradation in the upland tundra north of Inuvik, NWT. Field investigations were undertaken to characterize biotic and abiotic conditions and feedbacks in stable and degrading high-centre polygons. Field surveys were conducted along transects which crossed three polygon micropositions (centres, edges and troughs) and targeted a degradation sequence from stable troughs to ice wedge melt ponds. I measured surface microtopography, active layer depth, water depth, plant community composition, soil gravimetric moisture, late winter snow depth, and shallow annual ground temperatures. Field data showed that ice wedge degradation drove increases in soil moisture, standing water depth, ground surface collapse, ground temperature, and active layer thaw and snow pack compared to stable troughs. These changing abiotic conditions drove the shift from mesic upland tundra plant communities to unvegetated melt ponds. Interactions between abiotic and biotic factors in degrading troughs increase ground temperature and contribute to positive feedbacks for ice wedge degradation. Analysis of broad-scale factors affecting ice wedge degradation involved the mapping of high-centre polygon distribution across the study area and the distribution of ice wedge melt ponds using high-resolution aerial photographs from 2004. Recent changes in melt pond area were also mapped ...